2019
DOI: 10.1002/jcp.29158
|View full text |Cite
|
Sign up to set email alerts
|

PRR34‐AS1 overexpression promotes protection of propofol pretreatment against ischemia/reperfusion injury in a mouse model after total knee arthroplasty via blockade of the JAK1‐dependent JAK‐STAT signaling pathway

Abstract: Long noncoding RNAs have been documented to be protective against ischemia/ reperfusion (I/R) injury. However, few research works have focused on the protective effects of PRR34-AS1 on I/R injury after total knee arthroplasty (TKA).The objective of the present study was to investigate the possible effect of PRR34-AS1 on I/R injury after TKA. A mouse model with I/R injury after TKA was established. The interaction between PRR34-AS1 and Janus kinase 1 (JAK1) was examined and thoroughly investigated. Next, the ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 43 publications
0
7
0
Order By: Relevance
“…The MDA levels from B-HH to O-HH showed a MD of 1.80 nmol/L and 95% CI of 1.53 to 2.07 nmol/L (P<0.05). The ALT and AST levels had a MD of 8.24 IU/L and −11.73 IU/L, respectively, and the 95% CI was 6.43 to 10.06 IU/L and −14.04 to −9.43 IU/L, respectively (P<0.05) (15). The funnel charts of various indicators revealed that some of the circles were concentrated on the midline and were basically symmetrical with the midline, suggesting that the research accuracy was high and there was no bias in publication (16).…”
Section: Discussionmentioning
confidence: 96%
“…The MDA levels from B-HH to O-HH showed a MD of 1.80 nmol/L and 95% CI of 1.53 to 2.07 nmol/L (P<0.05). The ALT and AST levels had a MD of 8.24 IU/L and −11.73 IU/L, respectively, and the 95% CI was 6.43 to 10.06 IU/L and −14.04 to −9.43 IU/L, respectively (P<0.05) (15). The funnel charts of various indicators revealed that some of the circles were concentrated on the midline and were basically symmetrical with the midline, suggesting that the research accuracy was high and there was no bias in publication (16).…”
Section: Discussionmentioning
confidence: 96%
“…It has been previously reported that JAK/STAT signaling is involved in several important cellular processes, including cell proliferation, migration, apoptosis and inflammation (41)(42)(43). A number of studies have suggested that JAK/STAT signaling is involved in the pathogenesis of tissue and organ I/R injury, including intestinal I/R injury (22)(23)(24). By inactivating JAK/STAT3 signaling, dexmedetomidine was shown to inhibit the apoptosis of astrocytes induced by OGD/R (44).…”
Section: Discussionmentioning
confidence: 99%
“…JAK1 and JAK3 can activate STATs by phosphorylation (21). An increasing number of studies have suggested that the JAK/STAT signaling is involved in the pathogenesis of tissue and organ I/R injury, including intestinal I/R injury (22)(23)(24). Therefore, the present study aimed to investigate the role of Tofa and its possible regulatory effects on the JAK/STAT signaling pathway in intestinal I/R injury.…”
Section: Introductionmentioning
confidence: 99%
“…PRR34-AS1 (PRR34 antisense RNA 1) is an RNA gene affiliated with the long noncoding RNA (lncRNA) class ( Zhao et al, 2017 ; Tao et al, 2019 ). It has been reported that PRR34-AS1 is closely associated with the early tumor recurrence in bile duct cancer ( Fang et al, 2020 ), and it has been proved to potentially relieve ischemic reperfusion injury after total knee arthroplasty in mice by diminishing apoptosis and enhancing cell proliferation of chondrocyte in vitro ( Fang et al, 2020 ). In our research, the expression level of PRR34-AS1 was negatively correlated with nearly all immune cells and its overexpression indicated a higher risk to be diagnosed as AR patients, which may suggest a novel insight into the relationship between gene and cells.…”
Section: Discussionmentioning
confidence: 99%